1998
DOI: 10.1109/95.679028
|View full text |Cite
|
Sign up to set email alerts
|

Materials characterization, conduction development, and curing effects on reliability of isotropically conductive adhesives

Abstract: Three commercially available, silver filled, snap cure isotropically electrically conductive adhesives for surface mount applications were selected for study. Fundamental material characterizations were conducted on these materials, including thermal analysis [differential scanning calorimetry (DSC), thermo-gravitational analysis (TGA), and thermo-mechanical analysis (TMA)], rheological, and dynamic mechanical analyses. Microstructural investigations [scanning electron microscopy (SEM), transverse electromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 9 publications
(8 reference statements)
0
19
0
Order By: Relevance
“…7,8 The present authors 8 have previously investigated the effect of curing conditions on the electrical properties of isotropic conductive adhesives (ICAs) composed of an epoxy-based binder, and we found that the electrical resistance of ICA specimens appears to decrease during the curing and cooling processes. The decrease in the electrical resistance is suggested as being caused by shrinkage of the adhesive binder, 9,10 accompanied by accumulation of internal stress. 11,12 The electrical resistivity of the cured ICA tends toward a certain value (which differs depending on the curing temperature) with increasing degree of conversion.…”
Section: Introductionmentioning
confidence: 98%
“…7,8 The present authors 8 have previously investigated the effect of curing conditions on the electrical properties of isotropic conductive adhesives (ICAs) composed of an epoxy-based binder, and we found that the electrical resistance of ICA specimens appears to decrease during the curing and cooling processes. The decrease in the electrical resistance is suggested as being caused by shrinkage of the adhesive binder, 9,10 accompanied by accumulation of internal stress. 11,12 The electrical resistivity of the cured ICA tends toward a certain value (which differs depending on the curing temperature) with increasing degree of conversion.…”
Section: Introductionmentioning
confidence: 98%
“…1-3 A number of research articles about the electrical properties of metal-filled polymer composites have been reported. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] It was found that the interface between the metal fillers is one of the major factors that could degrade the electrical property of the polymer composite. 16,17 One of the approaches to minimize the interface is to make these fillers fuse with each other.…”
Section: Introductionmentioning
confidence: 99%
“…The ICAs satisfy the requirements for lead-free (green, environmentally friendly) interconnects, and their processing temperature is considerably lower (100-150°C ) than that of eutectic (220-230°C ) or lead-free solders, such as SnAg (96.5%/3.5% by weight, respectively) and SnAgCu (96.1%/3.2%/0.7% by weight, respectively). [1][2][3][4][5][6][7][8][9][10][11][12] Therefore, many efforts have been dedicated to apply ICAs in the board-assembly process as an interconnect material. While ICAs have many advantages over eutectic and lead-free solders, there are some technical challenges to overcome, such as unstable contact resistance under extremely humid conditions, low electrical conductivity, low impact strength, and low self-alignment capability.…”
Section: Introductionmentioning
confidence: 99%